The concept of ‘first-generation student’ in the literature: Implications for South African higher education - Heymann, L; Carolissen, R (South African Journal of Higher Education, 2011)
In the United States first-generation students (FGSs), those who are the first in their families to attend university, are recognised as disadvantaged and receive government support. Amidst affirmative action debates in higher education in South Africa, an increased awareness has emerged about challenges that FGSs in this country face. A systematic review was done to provide a summary of the literature about FGSs. The key phrase ‘first-generation student’ was entered on the online databases JSTOR, Academic Search Premier: Ebscohost, Proquest, PsychInfo, SAE Publications and Scopus. This search yielded 59 articles and a thematic analysis was conducted. Themes that arise suggest that identifying FGSs can make a valuable contribution towards assisting institutions of higher education (HE) in South Africa in the debate about who vulnerable students may be in order to provide them with support for success in higher education. However, FGS status is just one amongst a number of factors that may impact on student experiences in HE.